Penerapan Konsep Land Banking di Indonesia untuk Pembangunan Perumahan MBR di Kawasan Perkotaan - Noegroho, Noegi (Bina Nusantara University, 2012)
In line with the increase of population, the need for housing continues to increase as well. This is a classic issue in urban areas when land prices continues to rise so that some recidences belongs only to high society The concept of Land Banking could be as one solution to acquire land which is feasible to be built for low income housing. This paper discusses about the concept of land banking and how it is applied in Indonesia.